LEKSIKON TUMBUHAN DALAM SERUMPUN BERPANTUN MELAYU - Chika Aprilia; Laurensius Salem; Agus Syahrani (Universitas Tanjungpura, 2022)
AbstrackThis study aims to classify the form of the lingual unit, describe its meaning and function, and produce a supplementary form of Indonesian language learning text based on the plant lexicon in the Pontianak Malay rhyme cognate. The method used in this research is descriptive qualitative method. The sources of data in this study are video documentation and the Pontianak Malay community who are located in Sungai Beliung Village, West Pontianak. Data collection techniques, namely, documentation techniques, interviews, notes, and records. The technique of testing the validity of the data is the persistence of observation and peer examination. This study contained 135 rhyme data based on the plant lexicon, then 90 lexicon of plant names and plant parts and 69 based on the lexicon of plant names. The form of the lingual unit contains 18 monomeric data, and 72 phrase data. In addition, there are 90 plant lexicon based on lexical meaning and 80 data on cultural meaning. The form of Indonesian language learning text b ased on the plant lexicon in the Pontianak Malay rhyme cognate produces descriptive text.Keywords: Lexicon, Plants, Pantun, Pontianak Malay